Ghost summer : stories - Due, Tananarive, 1966- (Prime Books, 2015)
"In her debut collection of short fiction, Due takes us to Gracetown, a small Florida town that has both literal and figurative ghost; into future scenarios that seem all too real; and provides empathetic portraits of those whose lives are touched by Otherness. Featuring an award-winning novella and fifteen stories" --